Pengaruh Strategi Promosi dan Harga Terhadap Keputusan Pembelian Konsumen Melalui Brand Awareness Sebagai Variabel Intervening Pada Cv. Raksa Stone - Abdillah, Rahman Karunia Sandi; Sumiati, Siti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the effects of promotion strategy and price on consumer purchase decisions, with brand awareness as an intervening variable at CV Raksa Stone. An explanatory quantitative approach was employed. Data were collected through questionnaires distributed to 160 consumers who had purchased natural stone products between 2022 and 2024, using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.The results indicate that promotion strategy has a positive and significant effect on both brand awareness and purchase decisions. Price also shows a positive and significant effect on brand awareness and purchase decisions. Furthermore, brand awareness has a significant influence on consumer purchase decisions. Mediation analysis reveals that brand awareness successfully mediates the relationship between promotion strategy and purchase decisions, but does not mediate the relationship between price and purchase decisions.These findings suggest that promotion strategy plays a key role in enhancing brand awareness, which in turn drives consumer purchasing decisions. In contrast, price tends to influence purchase decisions directly rather than indirectly through brand awareness. This implies that while competitive pricing remains important, promotional efforts are more effective in building brand awareness and shaping long-term consumer decision-making.The study offers practical implications for management, highlighting the importance of optimizing promotional strategies to strengthen brand awareness while maintaining competitive pricing to support stable purchase decisions in the natural stone industry.